Assessments of two-pore channel 2 in the human MDAMB-231 breast cancer cell line: from the aspects of bibliometric, proliferation, apoptosis, and chemosensitivity / Nelofar Sediqi - Sediqi, Nelofar (2022)
Two-pore channel 2 (TPC2) is an endolysosomal calcium channel that governs physiological functions in cellular and organism levels such as angiogenesis, pH regulation, and autophagy. Recent findings demonstrated the implication of TPC2signalling in cancer hallmarks and chemoresistance. TPC2 is recognised as a cancer driver and played role in the different cancer-related processes. However, the role ofTPC2 in breast cancer and its ability to modulate the sensitivity of cancer cells to chemotherapy remains to be elucidated. Further, although TPC2 research is becoming more popular around the world, no studies using bibliometric methodologies to assess the overall characteristics of TPC2 research have been conducted. Generally, this study was designed to assess TPC2 from two different views; the bibliometrics perspective and the in vitro characterisation. From the bibliometric aspect, this study aimed to find out the global research on TPC2 via bibliometric analysis. The Scopus database, VOSviewer, Harzing's Publish or Perish and Openrefine tools were used for this aim. For the in vitro characterisation, this study intended to determine the roles of TPC2 on the proliferation and apoptosis of MDA-MB-231 cells, an in vitro model of triple negative breast cancer (TNBC). The functional roles of TPC2 in MDA-MB-231 cells were explored using siRNA-mediated gene silencing. MTS assay was used to evaluate the effect of TPC2 silencing on the proliferation of MDA-MB-231 cells, and flowcytometry was employed to measure apoptosis. Furthermore, this study designed to elucidate the effect of TPC2 silencing on doxorubicin-induced cytotoxicity in MDAMB-231 cells. Prior to doxorubicin treatment, expression of TPC2 in MDA-MB-231cells was silenced. This was followed by an MTS assay to evaluate the effect of TPC2silencing on doxorubicin's cytotoxic activity in MDA-MB-231 cells and Annexin V/PI flow cytometry for apoptosis assay. Moreover, to probe for the mechanisms of apoptosis, the expression of several apoptotic markers namely Bcl2, Tp53, and Bax were evaluated by qPCR. The bibliometric findings indicated that the total publication on TPC2 was increasing in 2021. The United Kingdom (UK) and the University of Oxford were the leading country and institution in TPC2 research. The in vitro results showed that TPC2 suppression did not influence the proliferation and apoptosis ofMDA-MB-231 cells (p>0.05). Likewise, its inhibition did not have any effect on the chemosensitivity of doxorubicin in MDA-MB-231 cells (p>0.05). However, the MTS assay's results displayed that doxorubicin significantly reduced the proliferation ofMDA-MB-231 cells. Following this, the Annexin V/PI flow cytometry's findings confirmed the results of the MTS assay which represented that doxorubicin treatment associates with a high number of apoptotic, and necrotic cells (p<0.05). Moreover, gene expression assay data exhibited the molecular mechanisms involved in cell death. The findings indicated that cell death was possibly related to a significant reduction of theBcl2 level, and the significant enhancement of the Bax (p<0.05). Overall, our findings add to our knowledge of the TPC2 research worldwide. It opens up new opportunities for future research, particularly in the fields of oncology, autophagy and COVID-19.Furthermore, our discoveries shed light on TPC2 role in proliferation, apoptosis, and chemosensitivity in MDA-MB-231 cells. Future research on TPC2 in MDA-MB231cells may want to apply a longer timeline and focusing on other cancer hallmarks apartfrom what have been assessed in the current study.